Wilson's Creek, Pea Ridge, and Prairie Grove : a battlefield guide, with a section on Wire Road - Hess, Earl J.; Brest, Christopher Lawrence, 1950- (This hallowed ground., 2006)
Wilson's Creek, Pea Ridge, and Prairie Grove were three of the most important battles fought west of the Mississippi River during the Civil War. They influenced that region by shaping Union military efforts while contributing to Confederate defeat. This book provides a detailed guide to these battlefields, and the major sites of each engagement.